Photoacclimation and Photoprotection of Juvenile Sporophytes of Macrocystis pyrifera (Laminariales, Phaeophyceae) Under High-light Conditions During Short-term Shallow-water Cultivation1 - Umanzor, Schery (Journal of phycology, 2020)
© 2019 Phycological Society of America.